Bridegroom Nile and Bride Egypt (PSI VII 845r = XXXIX 1–11 Heitsch = 43(A) Perale) - Bartol, Krystyna (Polskie Towarzystwo Filologiczne, 2021)
The article discusses some questions related to the interpretation of the hexametric poem preserved on the recto of PSI VII 845. An important issue here is the relationship between the fragment on the papyrus and the epithalamic literary tradition.